Meningkatkan Hasil Belajar Siswa Menggunakan Model Pembelajaran Kooperatif Tipe Stad Pada Pembelajaran IPA Kelas Vi Sd Negeri Lasoani - Vika Novita Makawimbang; Nasrullah Nasrullah; Arif Firmansyah (JURNAL DIKDAS, 2025)
This research aims to improve the learning outcomes of Grade VI students at SD Negeri Lasoani in Social Studies through the application of the STAD cooperative learning model. This study uses the Classroom Action Research (CAR) method, often referred to as PTK in Indonesia. The focus of this research is on efforts to improve the quality of learning and the educational process in the classroom through actions or strategies implemented by the teacher. In Cycle I, student learning outcomes were still low, so a reflection was conducted to address the identified shortcomings. In Cycle II, after improvements were made, 17 out of 20 students (85%) achieved mastery, meeting the research success criteria (70%). The teacher communicated the results of Cycle I to the students, identified the weaknesses, and encouraged students to be more active in learning so that their learning outcomes would improve. The research results show an improvement in student learning outcomes using the STAD cooperative learning model in Social Studies for Grade VI students at SD Negeri Lasoani. In Cycle I, the classical mastery percentage reached 50%, while in Cycle II it increased to 80%, with a percentage score of 70%. The use of this model successfully improved student learning outcomes and created a fun, active, creative, and innovative learning atmosphere.